THE ANALYSIS OF PRICE FAIRNESS AND SERVICESCAPE ON CUSTOMER SATISFACTION AT UP CREATIVE SPACE AND COFFEE MANADO - Febyola Kawatu; David P. E. Saerang; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of price fairness and servicescape on customer satisfaction at UP Creative Space and Coffee Manado. This study uses quantitative methods and uses multiple linear regression tests to determine the effect of price fairness and servicescape on customer satisfaction. The sample of this research is 100 respondents. The sampling technique used is purposive sampling and the data collection method is in the form of a questionnaire run through the Google Form. Testing and the data analysis in this study using SPSS 25 software. The results of this study indicate that price fairness (X1) partially has a positive and significant effect on customer satisfaction (Y). servicescape (X2) partially has a positive and significant effect on customer satisfaction (Y). Price fairness (X1) and servicescape (X2) simultaneously have a positive and significant effect on customer satisfaction (Y). The R square value obtained from the results of the coefficient of determination (R2) of 0.768 explains that 76.8% of customer satisfaction can be explained by price fairness and servicescape. Meanwhile, the remaining 23.2% is influenced by other variables not examined in this study   Keywords: price, fairness servicescape, and customer satisfaction